The Influence of Performance Appraisal System Toward Work Motivation and Performance of Five Star Hotels Employees in Yogyakarta - Zainal Mustafa Eq (Jurnal Aplikasi Manajemen, 2010)
The study aims to determine the extent to which performance appraisal system that have been carried out affect the employee’s performance of five star hotels in Yogyakarta, with work motivation as a variable. Theoretically, hypothesis underlying the objectives will be analyzed by path analysis, the processing using AMOS software. Analytical results show that 1) descriptively, it can be concluded that all variables already considered quite good although not as expected leadership, 2) indirectly, the dimensional rating system has a strong and significant influence on performance of employee if the work motivation to be variable, 3) appraiser on appraisal work indirectly through the variable of work motivation is the variable that most strongly influence the employee performance.Keywords: Performance appraisal, motivation, and performance.